Role of aluminum doping on phase transformations in nanoporous titania anodic oxides - Bayata, Fatma; Urgen, Mustafa (Elsevier Science Sa, 2015)
The role of aluminium doping on anatase to rutile phase transformation of nanoporous titanium oxide films were investigated. For this purpose pure and aluminum doped metal films were deposited on alumina substrates by cathodic arc physical deposition. The nanoporous anodic oxides were prepared by porous anodizing of pure and aluminum doped titanium metallic films in an ethylene glycol + NH4F based electrolyte. Nanoporous amorphous structures with 60-80 nm diameter and 2-4 mm length were formed on the surfaces of alumina substrates. The amorphous undoped and Al-doped TiO2 anodic oxides were heat-treated at different temperatures in the range of 280-720 degrees C for the investigation of their crystallization behavior. The combined effects of nanoporous structure and Al doping on crystallization behavior of titania were investigated using X-ray diffraction (XRD) and micro Raman analysis. The results indicated that both Al ions incorporated into the TiO2 structure and the nanoporous structure retarded the rutile formation. It was also revealed that presence or absence of metallic film underneath the nanopores has a major contribution to anatase-rutile transformation. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aluminum Doped Titania; Nanoporous Titanium Anodic Oxide; Anatase To Rutile Phase Transformation; Tio2 Nanotube Arrays; Gas Sensor; Rutile Transformation; Anatase; Al; Surface; Films; Fabrication; Raman; Nanopowders